Struktur komunitas laba-laba di ekosistem padi ratun: pengaruh aplikasi Beauveria bassiana (Balsamo) - Herlinda, Siti; Dewi, Rafika; Adam, Triani; Suwandi, Suwandi; Wijaya, Andi (Jurnal Entomologi Indonesia, 2016)
Spiders are the main predators in paddy ecosystem. Application of entomopathogenic fungus, such as Beauveria bassiana (Balsamo) is not expected to have any negative effect on spiders in the paddy field. This research was aimed to compare species composition, abundance, and species richness of spiders in ratoon paddy. The research was done on three hectares of rice fields that were treated with the following treatment, (i) 2 L/ha/application of liquid B. bassiana, (ii) 2 L/ha/application compost extract (without liquid B. bassiana), and (iii) a combination of liquid B. bassiana and compost extract with each using the same 2L/ha/application dose. The result of this research showed that B. bassiana bioinsecticide application did not affect the abundance and species richness of spiders in ratoon paddy. The treatments did not significantly affect species richness and abundance of the canopy-inhabiting spiders. The species richness and abundance of the soil-dwelling spiders on the paddy field applied by the bioinsecticide was not different from those without the bioinsecticide. The treatments did not effect species composition of the canopy-inhabiting and the soil-dwelling spiders. Application of B. bassiana bioinsecticide was not harmful for the spiders in the rice field.